MELKONYAN RUBEN, POGHOSYAN NAIRA, THE ARMENIAN QUESTION AND ARMENIAN GENOCIDE IN THE MEMOIRS OF HIGH-RANKED TURKISH POLITICIANS AND MILITARY OFFICERS (THE END OF XIX- MID OF XX), YEREVAN 2022, 110 P. (Journal of Oriental Studies, 2024)
Գրախոսությունը նվիրված է Ռ․ Մելքոնյանի և Ն․ Պողոսյանի Հայկական հարցն ու Հայոց ցեղասպանության խնդիրը թուրք բարձրաստիճան քաղաքական և ռազմական գործիչների հուշերում (XIX դարի վերջ-XX դարի կեսեր) գրքին։
Keywords: Ottoman Empire; military and political activists; memoires; Armenian Subject